Analisis Rasio Profitabilitas (ROA) pada Bank Victoria Syariah Periode 2020–2024 - Aqil, Bima Labibul; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
This study analyzes the profitability performance of Bank Victoria Syariah during the 2020–2024 period using the Return on Assets (ROA) ratio as the main indicator. Financial data were obtained from the bank’s audited annual reports and evaluated through quantitative analysis. The results show fluctuating ROA values throughout the five-year period, with a significant improvement from 2022 to 2024. These changes reflect variations in asset growth, operational efficiency, and income performance. The upward trend in ROA during the final years indicates improved asset utilization and enhanced profitability as the bank prepared for its rebranding into Bank Syariah Nasional (BSN). This study contributes to the understanding of financial performance in Islamic banking and provides practical insights for strengthening profitability management.